Invasive species management: an animal ethics perspective - Tuminello, Joseph A., author; Rollin, Bernard, advisor; McShane, Katie, committee member; Archibeque, Shawn, committee member (Colorado State University. Libraries, 2012)
In the scholarly literature on invasive species management, there exists a tendency to neglect the moral relevance of sentience when determining best possible management strategies regarding sentient members of invasive species. In addition, there is also a negative bias against invasive species, where such species are viewed as inherently "bad." Because of this negative bias, many wildlife managers, conservation biologists, and ecologists share the default view that invasive species are nuisances and must be gotten rid of, using the most cost-effective and efficient means possible. The neglect or omission of sentience within the literature often carries over into the implementation of invasive species management techniques, where sentient members of invasive species are often not treated as humanely as possible. In this thesis, I defend Bernard Rollin's animal ethic, where sentient beings are those capable of having interests, and which are also capable of self-valuation, which is necessary for possessing intrinsic value (on Rollin's view). Because such beings are capable of having interests which can be fulfilled or thwarted, they are objects of moral concern on this view. While I defend Rollin's view, any moral theory which considers sentience morally relevant at all will be compatible with the majority of my arguments regarding our treatment of sentient members of invasive species. If sentience is a morally relevant criterion, I argue that it continues to be so even when sentient beings are members of species which are considered to be "invasive." This claim is strongly supported by the large-scale vagueness and disagreement over terms such as "invasive," "native," and "exotic" within the literature. Because sentience is a morally relevant criterion when determining best possible management practices regarding invasive species, members of such species should be treated as humanely and in accordance with their respective telos as much as possible. Typically, this will entail prioritizing nonlethal and preventive methods of control over lethal methods. However, even when lethal control is deemed to be the best possible type of management strategy in a given situation, it should be implemented as humanely as possible. In addition to arguing for sentience as a morally relevant criterion when determining best possible management strategies regarding invasive species, I also argue that the negative bias against invasive species as inherently "bad" is ultimately unfounded. I support this claim by providing evidence of a variety of potential negative, positive, and neutral aspects of invasive species. Because invasive species are not inherently "bad" or "good," I argue that our attitudes toward and management of members of such species should be developed on a case-by-case basis. It is also important that the assessment of invasive species on a case-by-case basis be combined with the moral relevance of sentience. The bias against invasive species may serve to perpetuate the omission of sentience as a morally relevant criterion of invasive species management. The omission of sentience may also perpetuate the negative bias against invasive species. Understanding the moral relevance of sentience may help to diminish the negative bias against invasive species, and vice versa. After considering and responding to several objections to my arguments, I provide an overview of different sorts of lethal, nonlethal, and preventive methods of invasive species management, and discuss how each of these can be implemented in a more humane fashion, in order to present ways in which my arguments and view can be successfully applied in a variety of real-world scenarios.
Keywords: animal ethics; wildlife management; invasive species; environmental ethics